Effects of Bacillus thuringiensis RZ2MS9 on soybean (Glycine max) considering volatile organic compounds, plant development in the field, and soil microbiome diversity - Oliveira, Helena Gutierrez (2021)
Soil microorganisms are of great importance to the sustainability of ecosystems. In agriculture, the use of plant growth-promoting rhizobacteria as bioinoculants represents an environmentally friendly alternative to improve crop yield since those bacteria are generally helpful for plant growth and protection. Among those rhizobacteria, Bacillus thuringiensis (Bt) is known as an important agent of insect control. However, it has been recently described also as a plant-growth promoter that is able to colonize plants and improve host fitness. Thus, the present research evaluated different aspects of the interaction between soybean and a plant growth-promoting rhizobacterium Bt RZ2MS9, through both in vitro and field assays. In chapter 1, a general introduction was presented. Chapter 2 discussed a field study in which soybean seeds were inoculated with Bt RZ2MS9 and subsequently analyzed for plant development and productivity among treatments with or without chemical treatment and inoculation. The biocontrol potential of Bt RZ2MS9 was evaluated by recording stink bug (Piezodorus guildinii and Euchistus heros) population density and severity of phytopathogenic fungi occurrence through a diagrammatic scale of leaf damage. We also analyzed the in vitro effects of the bacterial strain on the feeding habits of P. guildinii. The strain Bt RZ2MS9 was able to improve soybean plant height and slightly increase crop yield. Groups that received chemical treatment showed an increased dry mass, green stem, and leaf retention. Dry mass did not differ between inoculated and non-inoculated groups. Infestation by stink bug P. guildinii showed a significant difference among treatments, but that was not observed for E. heros. There was a significant effect of the inoculation on the severity of leaf damage caused by phytopathogenic fungi (mainly Cercospora kikuchii). A feeding choice study with P. guildinii showed preference to material without the strain. Chapter 3 presents an analysis of the volatile compounds released by Bt RZ2MS9, the effects of these compounds on the germination and development of soybean seeds, and on the phytopathogenic fungal mycelia growth. Volatile compounds produced by the strain had a significant effect on the soybean germination process but not on the growth of the fungi studied. Chapter 4 presents the analyzes of the effects of Bt RZ2MS9 inoculation on the microbiome community through metagenomics of soil samples collected before, during, and after soybean crop management applying both the strain assessed here and Bradyrhizobium japonicum in co-inoculation. Co-inoculation decreased plant lodging significantly but had no effect on crop productivity. The microbiome analysis showed that inoculation did not interfere in the diversity of microorganisms during the crop cycle, but treatments inoculated with Bt RZ2MS9 had a lower Chao1 diversity index 15 days after the crop cycle. The assessment of features from new PGPRs is of great importance to the development of new strategies to improve sustainability in crop management. Further experimentation on this strain in different crops, and field conditions, besides analysis of its metabolites and genes associated with them, may unravel new biotechnology alternatives for integrated crop management